2012
DOI: 10.1212/wnl.0b013e3182574f50
|View full text |Cite
|
Sign up to set email alerts
|

Clinical assessment of noninvasive intracranial pressure absolute value measurement method

Abstract: The proposed noninvasive ICP measurement method is precise and accurate compared with gold standard CSF pressure measured via lumbar puncture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
76
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(90 citation statements)
references
References 31 publications
4
76
0
3
Order By: Relevance
“…4 Absolute ICP noninvasive measurements of hundreds of healthy volunteers, and neurologic and traumatic brain injury patients showed that our technology can be used on more than 96% of individuals independently of age, gender, or intracraniospinal pathology. Physiologic findings 1,4,6 of OA reaction to ICP and pressure on the orbit fully support conclusions of an anatomical study, 5 which showed that the intracranial course of OA may be absent in just 5% of individuals. The authors assume that extracranial OA blood flow is independent of ICP.…”
supporting
confidence: 66%
See 2 more Smart Citations
“…4 Absolute ICP noninvasive measurements of hundreds of healthy volunteers, and neurologic and traumatic brain injury patients showed that our technology can be used on more than 96% of individuals independently of age, gender, or intracraniospinal pathology. Physiologic findings 1,4,6 of OA reaction to ICP and pressure on the orbit fully support conclusions of an anatomical study, 5 which showed that the intracranial course of OA may be absent in just 5% of individuals. The authors assume that extracranial OA blood flow is independent of ICP.…”
supporting
confidence: 66%
“…1 We respectfully disagree with the assumption that "pressure on the orbit does not balance transmural pressure in the segments of ophthalmic artery (OA)." Statistically significant evidence-based results of clinical 1,4 and healthy volunteer 5 studies show that this assumption has no scientific background. Dr. Heyreh 5 demonstrated that intracranial segment (IOA) of the OA is absent in 5% of humans.…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…Obtaining CSF for analysis may be the only way to confirm subarachnoid hemorrhage, meningitis and neuro-inflammatory diseases (Ragauskas et al, 2012).…”
mentioning
confidence: 99%
“…Blood flow in both segments of the OA depends on ICP, ambulatory blood pressure, heart rate, intraocular pressure, intraorbital pressure, and other factors. 1 The benefit of our method is in the equilibration of ICP with Pe. The balance ICP 5 Pe is not dependent on influential factors.…”
mentioning
confidence: 99%